Study on Fault Signal Characteristics of an Induction Motor During Interturn Fault - Surakit Thongsuk; Atthapol Ngaopitakkul (My University, 2014)
This paper aims to measure and analyze the behavior of the fault current when the interturn fault occurs between turns in three-phase induction motors. A 3-HP induction motor is used in the experiment setup to study the effects of a short circuit during the interturn fault occurrence. For induction motor, the winding of induction motor is divided into 5 positions so that the interturn fault signals can be obtained. The results from interturn fault characteristics study shown that current waveform during interturn fault has a sudden change and increases in short period of time. In addition, when interturn fault occurs, the size of load and length of gap are influential factors that affect fault current, not the position of fault. Finally, the results obtained from the analysis will be beneficial in the development of a fault detection scheme.
Keywords: SIGNAL (programming language); Fault indicator; Machine Fault Diagnosis Techniques